A method for preparing a highly water-absorbent resin having improved gel strength and broad-spectrum UV resistance

By using materials such as vapor phase silica and nano zinc oxide in high-absorbent resins and combining organic ultraviolet absorbers, the problem of insufficient anti-ultraviolet performance of existing high-absorbent resins in extreme weather is solved, and gel strength and resistance to ultraviolet are achieved Significant performance improvements are applicable to a variety of industries.

CN114057943BActive Publication Date: 2025-01-10WEIFANG UNIV OF SCI & TECH

Patent Information

Application Number
CN202111428023.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-26
Publication Date
2025-01-10
Estimated Expiration
2041-11-26

AI Technical Summary

Technical Problem

The existing highly absorbent resins have insufficient UV resistance under extreme weather conditions, especially the UV light stabilizer does not absorb UV rays and is difficult to dissolve in water, which limits its application in the field of compound fertilizers.

Method used

Using vapor phase silica as an inorganic ultraviolet shielding agent and nano zinc oxide as crosslinking accelerator, combined with organic ultraviolet absorbers such as Avobenzon and UV-312 and UV-3638, a high-water absorption resin is prepared by a one-pot method to enhance it. Gel strength and broad-spectrum UV resistance.

Benefits of technology

It significantly improves the gel strength and UV resistance of high water absorption resin, and can effectively shield UV rays in the wavelength range of 280-400nm. It is suitable for extreme weather conditions and does not affect its high water absorption rate. It is suitable for agriculture, industry and sanitation industries. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114057943B_ABST
    Figure CN114057943B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a super absorbent resin with improved gel strength and broad-spectrum UV resistance, comprising the following steps: A, adding a neutralizer to an acrylic acid monomer, stirring while adding the neutralizer; B, after the reaction of step A is completed, carboxymethyl reed cellulose, acrylamide, fumed silica, nano zinc oxide, organic UV-resistant additive, crosslinking agent and oxidant are added in sequence, stirring and passing nitrogen, adding a reducing agent and then stirring the reaction; C, after the reaction of step B is completed, the temperature is raised to 90-100°C and kept warm for 1.5-2.5h, that is, the super absorbent resin prepared by the present invention has the advantages of high gel strength, wide UV-resistant wavelength range, good UV-resistant effect, high water absorption, simple process and low preparation cost, and the related product market is lacking, and has great application prospects in industries such as soil moisture retention, desert control, agriculture, forestry and flower transportation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a high-strength ultraviolet-resistant super absorbent resin for use in the fields of agriculture, forestry, flower cutting, desert greening and the like. Specifically, it relates to a method for preparing a super absorbent resin with improved gel strength and broad-spectrum ultraviolet resistance, wherein acrylic acid is used as a monomer, sodium hydroxide is used as a neutralizer, N,N-methylene acrylamide is used as a crosslinking agent, ammonium persulfate and sodium bisulfite are used as redox initiators, fumed silica is used as an inorganic ultraviolet shielding agent, a gel strength improver, and a surface crosslinking agent, N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and avobenzone are used as composite organic ultraviolet absorbers, and a one-pot method is used to prepare a super absorbent resin with improved gel strength and broad-spectrum ultraviolet resistance, and the water absorption rate thereof is 800-1300 g / g. Background Art

[0002] Super absorbent resin is a polymer material with a three-dimensional network structure that contains a large number of hydrophilic groups such as carboxyl and hydroxyl groups through appropriate cross-linking. It is a new type of functional polymer material developed since the 1960s. It is insoluble in water and organic solvents, and has the ability to absorb hundreds or even thousands of times its own weight of water. It absorbs water quickly and has good water retention performance. It is difficult to separate water even under pressure, and has good stability to light, heat, acid and alkali. It is widely used in many fields such as health care, agriculture, gardening, petrochemicals, civil engineering and medical and health care, especially in agriculture, forestry, gardening and medicine and health care, and has become an indispensable material.

[0003] The research and development of super absorbent resins has only a few decades of history. The earliest country to develop and use super absorbent resins was the United States. From the late 1960s to the 1970s, American Grain-Processing, Hercules, Japanese Sumitomo Chemical, Sanyo Chemical and other companies, as well as some companies in Germany, France and other countries around the world conducted a lot of research on the varieties, manufacturing methods, properties and application fields of super absorbent resins, and made significant progress. The greatest achievements were made by the United States and Japan, followed by Germany and France.

[0004] In the 1980s, the use of derivatives of other natural products to prepare water-absorbent materials, such as alginate, protein, cellulose, etc., began to appear. Although their water absorption rate is still low, these new methods provide new research ideas for opening up new types of water-absorbent resins. At the same time, the research on highly absorbent composite materials obtained by combining highly absorbent materials with other inorganic or organic substances also began to take off. Since composite resins can improve the water absorption rate, gel strength and other properties of water-absorbent materials, they have developed rapidly.

[0005] Since the 1990s, the research on super absorbent resins has made great progress. At present, the United States, Japan, Russia, Israel, Egypt and other countries have invested a lot of money in the development and application of super absorbent resins. According to statistics, the world's super absorbent resin production in 1989 was 26×104 t, of which the United States was 105,000 tons and Japan was about 76,000 tons. By 2000, the United States' super absorbent resin production reached 500,000 tons and Japan's production reached 400,000 tons. Because super absorbent resins have strong water absorption and water retention properties, they can absorb sufficient water when there is more water, and slowly release it in drought to meet the needs of plant growth. After releasing water, super absorbent resins are easily decomposed into organic matter, which can increase the fertilizer efficiency of the soil, improve the soil's aggregate structure, and provide the necessary conditions for plant growth. Therefore, they are widely used in the fields of flower cultivation and seedling cultivation to promote plant growth and increase plant growth rate.

[0006] Super absorbent resin is widely used in various aspects of medical and health care due to its strong water absorption capacity, fast water absorption rate, good water retention capacity, softness after absorbing water, and not easy to dehydrate under certain pressure conditions. For example, it can absorb surgical and traumatic bleeding and secretions, and prevent suppuration of medical bandages, cotton balls and gauze; it is used in the production and manufacturing of medical supplies such as contact lenses and sustained-release drug substrates.

[0007] Taking advantage of the water-retaining and moisturizing properties of super absorbent resin, it can be used as an additive, moisturizer, thickener, etc. for daily cosmetics. When cosmetics containing absorbent gel are applied to the skin, the absorbent gel has extremely strong moisture absorption and moisturizing functions, which can keep the moisture in the cosmetics stably. When the human body sweats, the super absorbent gel can also absorb sweat to prevent the loss of cosmetics, so that people can keep a refreshing and lubricated state for a long time. Taking advantage of the adsorption and sustained release effects of the absorbent resin, spices can be added to the super absorbent resin to produce a fragrance-retaining material.

[0008] Super absorbent resins are also widely used in petrochemicals, such as oilfield treatment agents, dehydration of crude oil or refined oil, water plugging and profile control, heavy metal ion adsorbents, etc. For example, the large number of hydrophilic groups in the structure of super absorbent resins determine that they have high water absorption capacity, and they do not absorb hydrophobic hydrocarbon substances. Therefore, they can be made into profile control and water plugging agents, which can be injected into high permeability layers and swell when exposed to water to play a role in profile control. Super absorbent resin is a flexible polymer, and its gel after absorbing water will undergo reversible deformation under the action of external force. When used in the field of oil production, super absorbent resins can drive the remaining oil in the pores of the formation to migrate to the production wells under the action of external forces, thereby achieving an oil displacement effect.

[0009] Fumed silica is one of the most important high-tech ultrafine inorganic new materials. Due to its small particle size, it has a large specific surface area, strong surface adsorption, large surface energy, high chemical purity, good dispersion performance, and special properties in thermal resistance and electrical resistance. With its superior stability, reinforcement, thickening and thixotropy, it has unique characteristics in many disciplines and fields and plays an irreplaceable role. Fumed silica, commonly known as "ultrafine white carbon black", is widely used in various industries as an additive, catalyst carrier, petrochemical, decolorizer, matting agent, rubber reinforcing agent, plastic filler, ink thickener, metal soft polishing agent, insulation and thermal insulation filler, advanced daily cosmetic filler and spraying material, medicine, environmental protection and other fields. It also provides a new material foundation and technical guarantee for the development of related industrial fields. Because it shows special functions compared with conventional materials in terms of magnetism, catalysis, light absorption, thermal resistance and melting point, it has received great attention from people. Fumed silica can strongly reflect medium- and long-wave ultraviolet rays in the 280-400nm band, and has good dispersibility, making it a good inorganic ultraviolet shielding agent.

[0010] Nano zinc oxide is a multifunctional new inorganic material with a particle size of about 1 to 100 nanometers. Due to the refinement of the grains, its surface electronic structure and crystal structure change, resulting in surface effects, volume effects, quantum size effects, macro tunnel effects, high transparency, high dispersibility and other characteristics that macroscopic objects do not have. In recent years, it has been found that it exhibits many special functions in catalysis, optics, magnetism, mechanics, etc., making it have important application value in many fields such as ceramics, chemical industry, electronics, optics, biology, medicine, etc., and has special features and uses that ordinary zinc oxide cannot compare with.

[0011] UV absorber UV-312, whose scientific name is N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide, is a polar substance with low volatility and good thermal stability. It will not discolor when in contact with metal ions and is particularly effective for short-wavelength ultraviolet light. Therefore, it is often used as a whitening agent and stabilizer for UV light curing systems. UV absorber UV-3638, whose scientific name is 2,2′-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one, is a new generation of environmentally friendly and efficient UV absorber. It has high absorption of UV-B and UV-C. It has the characteristics of high molecular weight, low volatility, no color stain, high thermal stability, high temperature resistance, high pressure resistance, acid and alkali resistance, low usage, and high efficiency. It is an excellent UV absorber. Avobenzone, also known as 1-[4-(1,1-dimethylethyl)phenyl]-3-(4-methoxyphenyl)-1,3-propanedione, is a synthetic ultraviolet absorber and a good UV-A (>320nm) type ultraviolet absorber. It can block ultraviolet rays of the entire band (320~400nm). It is an efficient wide-spectrum UV-A filter. When combined with other UV-B sunscreens, it can provide full UV-A and UV-B protection and has a good ultraviolet radiation effect.

[0012] At present, the research on super absorbent resins focuses on reducing costs, improving gel strength, increasing water absorption, improving product salt resistance and suitability for use in extreme weather conditions such as deserts. These are mainly achieved through developing new synthesis processes, changing the type of initiator, changing raw materials, changing cross-linking agents and adding other additives. In particular, there are currently no related products for UV-resistant resins suitable for extreme weather conditions.

[0013] The patent with publication number CN 201310715577.6 discloses a multi-effect super absorbent resin fertilizer and a preparation method thereof, wherein the main steps are as follows: (1) placing acrylic acid and deionized water in a neutralization tank, slowly dripping potassium hydroxide solution into the neutralization tank using a dripping tube and stirring thoroughly, and after complete neutralization, maintaining the solution temperature between 40-50° C.; (2) adding hydroxyethyl acrylate, NN-methylenebisacrylamide, an antioxidant, an ultraviolet absorber and a light stabilizer to the neutralized solution, stirring thoroughly and mixing, and placing the reaction solution into a polymerization reactor. (3) continuing to add ammonium persulfate and sodium bisulfite solution into the polymerization reactor, turning on the ultraviolet lamp for irradiation to initiate the polymerization reaction, maintaining the polymerization temperature in the polymerization reactor between 70-80°C by temperature control, and ensuring that the polymerization reaction time reaches 1.5-2.5h; (4) drying and crushing the product obtained in the above step (3) to obtain a primary high molecular polymer; (5) placing the primary high molecular polymer obtained in the above step (4) in a mixer, and then adding ethylene glycol diglycidyl ether and glycerol aqueous solution into the mixer by spraying; In a mixing machine, ethylene glycol diglycidyl ether and glycerol aqueous solution are fully mixed with the primary high molecular polymer, and the mixing temperature is maintained between 50-60° C. and the mixing time is ensured to reach 0.5-1.5 hours, so that the surface of the high molecular polymer is fully cross-linked to obtain a highly absorbent resin with antioxidant, light-resistant and anti-degradation properties; (6) Bacillus subtilis, Bacillus licheniformis, Bacillus laterosporus, Bacillus gelatinus, humic acid powder and bentonite are continuously added to the mixture obtained in step (5), and the mixture is fully stirred to obtain a powder or granules. A highly absorbent resin fertilizer rich in microbial agents that is resistant to oxidation, light and degradation; (7) adding bentonite, urea, ammonium phosphate and potassium sulfate to the mixture obtained in step (5), stirring the mixture thoroughly to obtain powder or granules, thereby obtaining a multi-effect highly absorbent resin fertilizer rich in nitrogen, phosphorus and potassium elements that is resistant to oxidation, light and degradation; (8) adding humic acid powder and bentonite to the mixture obtained in step (5), stirring the mixture thoroughly to obtain powder or granules, thereby obtaining a highly absorbent resin fertilizer rich in humic acid that is resistant to oxidation, light and degradation.

[0014] Although the patent uses the UV light stabilizer GW-540, this type of light stabilizer does not absorb ultraviolet rays. It is a hindered amine light stabilizer that captures free radicals and is insoluble in water. Because it is used in the field of compound fertilizers, the amount of anti-UV additives added is low and it is not suitable for use in extreme weather conditions. In addition, the patent additionally adds the antioxidant butylated hydroxyanisole (BHA), which is a type of oil-soluble antioxidant that is insoluble in water and is not suitable for the aqueous solution system of acrylic acid polymerization. The system adopted by the present invention uses a broad-spectrum inorganic ultraviolet shielding agent, fumed silica, which has a good shielding effect on UV-A and UV-B wavelengths, and an organic ultraviolet composite absorber, avobenzone (UV-A) and ultraviolet absorbers UV-312 and UV-3638 (UV-B), which has the effect of shielding and absorbing a wide range of dual wavelengths, and the selected reducing agent sodium bisulfite has an antioxidant effect, and no additional antioxidant needs to be added, and the fumed silica and sodium bisulfite have good water solubility and can be evenly dispersed in all parts of the super absorbent resin, and the performance is better than the oil-soluble antioxidant BHA of the existing patent document. It is particularly worth noting that the addition of ultraviolet shielding agents and ultraviolet absorbers will not significantly cause a decrease in the water absorption rate of the super absorbent resin, and will not limit its application field, which is an advantage that the existing patent document does not have. Summary of the invention

[0015] In view of the deficiencies of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a highly water-absorbent resin with improved gel strength and broad-spectrum anti-ultraviolet properties. The method comprises the following steps: using acrylic acid and acrylamide as comonomers, sodium hydroxide as a neutralizer, N,N-methylene acrylamide as a crosslinker, ammonium persulfate and sodium bisulfite as redox initiators, fumed silica as an inorganic ultraviolet shielding agent, a gel strength improver, and a surface crosslinking agent, nano zinc oxide as an inorganic ultraviolet shielding agent and a crosslinking accelerator, N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and avobenzone as a composite organic ultraviolet absorber, and adding carboxymethyl reed cellulose, and adopting a one-pot method to prepare a highly water-absorbent resin with improved gel strength and broad-spectrum anti-ultraviolet properties, wherein the water absorption rate is 800-1300 g / g.

[0016] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0017] The present invention provides a method for preparing a highly water-absorbent resin having improved gel strength and broad-spectrum UV resistance, comprising the following steps:

[0018] A. Add a neutralizing agent to the acrylic acid monomer and stir while adding the neutralizing agent;

[0019] B. After the reaction of step A is completed, carboxymethyl reed cellulose, acrylamide, fumed silica, nano zinc oxide, organic anti-ultraviolet additive, crosslinking agent and oxidant are added in sequence, stirred and ventilated with nitrogen, and then a reducing agent is added to react with stirring;

[0020] C. After the reaction in step B is completed, the temperature is raised to 90-100°C and kept warm for 1.5-2.5h to obtain the product.

[0021] Preferably, the neutralizing agent is sodium hydroxide; after the neutralizing agent is added in step A, the neutralization degree of acrylic acid is 30%-80%.

[0022] Preferably, the organic anti-ultraviolet additive is N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide, 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one and avobenzone.

[0023] Preferably, the cross-linking agent is N,N-methylenebisacrylamide;

[0024] The oxidizing agent is ammonium persulfate; the reducing agent is sodium bisulfite.

[0025] Preferably, the preparation method of the carboxymethyl reed cellulose comprises the following steps: mixing the crushed reed powder with a low concentration alkaline solution, stirring for 3-5 hours, then adding a high concentration alkaline solution and continuing to stir for 1-3 hours; then adding sodium chloroacetate to carry out an etherification reaction to obtain the carboxymethyl reed cellulose;

[0026] The degree of substitution of the carboxymethyl reed cellulose is 0.43.

[0027] Preferably, the low concentration alkaline solution is a 4-5% sodium hydroxide solution, and the high concentration alkaline solution is a 14-16% sodium hydroxide solution; the stirring temperature is 35°C;

[0028] The mass ratio of the reed powder to the alkali in the low-concentration alkali solution and the alkali in the high-concentration alkali solution is 100:22.5:30;

[0029] The reaction temperature of the etherification reaction is 75° C. and the reaction time is 2-3 hours; the mass ratio of the reed powder to sodium chloroacetate is 100:50.

[0030] Preferably, the mass ratio of the acrylic acid monomer, neutralizer, carboxymethyl reed cellulose, acrylamide, fumed silica, nano zinc oxide, organic anti-ultraviolet additive, crosslinking agent, oxidant and reducing agent is 30:5-13.5:5-10:6-12:0.3-1.5:0.1-0.8:0.09-0.9:0.09-0.45:0.25-0.6:0.25-0.6.

[0031] Preferably, the mass ratio of the oxidant to the reductant is 1:1; the mass ratio of N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-ethanediamide, 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one and avobenzone is 1:1:1.

[0032] Preferably, in step B, the stirring reaction temperature is 45°C.

[0033] The invention also provides a highly absorbent resin with improved gel strength and broad-spectrum UV resistance, comprising the following components in mass ratio: acrylic acid monomer, neutralizer, carboxymethyl reed cellulose, acrylamide, fumed silica, nano zinc oxide, organic UV resistance additive, crosslinking agent, oxidant and reducing agent in a mass ratio of 30:5-13.5:5-10:6-12:0.3-1.5:0.1-0.8:0.09-0.9:0.09-0.45:0.25-0.6:0.25-0.6.

[0034] Preferably, the neutralizing agent is sodium hydroxide;

[0035] The organic anti-ultraviolet additive is N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide, 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one and avobenzone in a mass ratio of 1:1:1;

[0036] The cross-linking agent is N,N-methylenebisacrylamide;

[0037] The oxidant is ammonium persulfate;

[0038] The reducing agent is sodium bisulfite;

[0039] The preparation method of the carboxymethyl reed cellulose comprises the following steps: mixing crushed reed powder with a low-concentration alkali solution, stirring for 3-5 hours, then adding a high-concentration alkali solution and continuing to stir for 1-3 hours; and then adding sodium chloroacetate to carry out etherification reaction to obtain the carboxymethyl reed cellulose.

[0040] Preferably, the degree of substitution of the carboxymethyl reed cellulose is 0.43.

[0041] Preferably, the low concentration alkaline solution is a 4-5% sodium hydroxide solution, and the high concentration alkaline solution is a 14-16% sodium hydroxide solution; the stirring temperature is 35°C;

[0042] The mass ratio of the reed powder to the alkali in the low-concentration alkali solution and the alkali in the high-concentration alkali solution is 100:22.5:30;

[0043] The reaction temperature of the etherification reaction is 75° C. and the reaction time is 2-3 hours; the mass ratio of the reed powder to sodium chloroacetate is 100:50.

[0044] The fumed silica used in the present invention is nano-scale hydrophilic silica (200 m 2 / g), in the present invention, it is used as an inorganic anti-ultraviolet shielding agent, a gel strength enhancer and a surface cross-linking agent.

[0045] The monomers used in the invention are acrylic acid and acrylamide dual monomers, the matrix is ​​carboxymethyl reed cellulose, and the prepared high water-absorbent resin is a polyacrylic acid-polyacrylamide graft copolymer type high water-absorbent resin.

[0046] The polymerization method adopted by the present invention is free radical polymerization in aqueous solution, without adding any organic solvent, and the excess sodium bisulfite acts as an antioxidant, and no additional antioxidant needs to be added.

[0047] The whole synthesis process of the present invention adopts a one-pot preparation method, nitrogen is passed to deoxygenate, and the polymerization temperature is 45°C.

[0048] The water-absorbing resin prepared by the invention has high strength and broad-spectrum anti-external-ray performance, can be suitable for ultraviolet light with a wavelength of 280-400nm, and can be used in industries with special requirements on the strength of high water-absorbing resin.

[0049] The highly water-absorbent resin prepared by the present invention has the advantages of high gel strength, wide UV resistance wavelength range, good UV resistance effect, high water absorption rate, simple process and low preparation cost, etc., and there is a lack of relevant product market. It has great application prospects in industries such as soil moisture retention, desertification prevention and control, agriculture, forestry and flower transportation.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The highly water-absorbent resin with improved gel strength and broad-spectrum UV resistance prepared by the method of the present invention can be widely used in agriculture, industry, health industry, forestry, flower industry, etc., and is particularly suitable for desert areas with extreme weather. It can be used for soil and water conservation, change the soil aggregate structure, increase the water permeability and air permeability of the soil, and can also be used for desert prevention and control, plant afforestation, and water conservation. At the same time, it provides the nutritional elements required by plants and has important market application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0053] Figure 1 It is a process flow chart for preparing a highly absorbent resin with improved gel strength and broad-spectrum UV resistance;

[0054] Figure 2 This is the influence curve of the mass ratio of matrix (carboxymethyl reed cellulose) and monomer (the total amount of acrylic acid and acrylamide) on the water absorption rate of super absorbent resin;

[0055] Figure 3 This is the curve showing the effect of the mass ratio of acrylic acid and acrylamide on the water absorption rate of super absorbent resin;

[0056] Figure 4 It is the effect curve of the degree of neutralization of acrylic acid on the water absorption rate of the super absorbent resin with improved gel strength and broad-spectrum UV resistance;

[0057] Figure 5 It is the effect curve of the amount of cross-linking agent on the water absorption rate of the highly absorbent resin with improved gel strength and broad-spectrum UV resistance;

[0058] Figure 6 This is the effect curve of the initiator dosage (fixed ammonium persulfate to sodium bisulfite mass ratio of 1:1) on the water absorption rate of the super absorbent resin with improved gel strength and broad-spectrum UV resistance;

[0059] Figure 7 It is a comparative picture of ultraviolet aging experiment between the super absorbent resin with improved gel strength and broad-spectrum ultraviolet resistance prepared by the present invention and the common super absorbent resin. DETAILED DESCRIPTION

[0060] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0061] The specific preparation method of the high water-absorbent resin with broad-spectrum anti-ultraviolet performance described in the following examples is as follows:

[0062] The first step is the preparation of carboxymethyl cellulose:

[0063] The dried reeds were crushed, ground, and sieved through a 100-mesh sieve to obtain fine powder. 100 g of the fine powder was evenly dispersed in 500 mL of a 4.5% sodium hydroxide aqueous solution, then moved to a 35°C constant temperature water bath and stirred and heated for 4 hours. Then, 200 mL of a 15% sodium hydroxide solution was added thereto, and the stirring reaction was continued for 2 hours. Then, the temperature of the water bath was increased to 75°C, and then 250 mL of a 20% sodium chloroacetate solution was added thereto. After reacting for 2.5 hours, the reaction solution was taken out and placed on a drying tray, dried in a 70°C constant temperature drying device for 48 hours, then crushed and sieved through a 120-mesh sieve. The degree of substitution was measured to be 0.43, which was the carboxymethyl reed cellulose used in the experiment.

[0064] Step 2: Raw material processing

[0065] First, industrial-grade acrylic acid is passed through a tightly packed 200-mesh alumina column to remove the inhibitor;

[0066] Then prepare a 10% sodium hydroxide solution and set it aside for later use, prepare a 16% sodium bisulfite solution, and store it in a sealed container filled with nitrogen.

[0067] The third step is polymerization reaction experiment (such as Figure 1 (shown)

[0068] At 0°C, add 30 parts of acrylic acid monomers from which the inhibitor has been removed into the reaction container, add 50-135 parts of a 10% sodium hydroxide solution prepared in advance into the acrylic acid dropwise, so that the neutralization degree of the acrylic acid is 30%-80%, and stir while dropping until the temperature returns to room temperature. Then add 5-10 parts of carboxymethyl reed cellulose, 6-12 parts of acrylamide, 0.3-1.5 parts of fumed silica powder and 0.1-0.8 parts of nano zinc oxide powder into the neutralized solution, stir evenly, and then add 0.03-0.3 parts of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.03-0.3 parts of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.03-0.3 parts of avobenzone. After stirring for 20 minutes, add 0.090-0.450 parts of cross-linking agent N,N-methylenebisacrylamide and 0.25-0.60 parts of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.25-0.60 parts) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 1.5-2.5 hours. After the reaction is completed, place the prepared super absorbent resin in an oven to dry for 48 hours and crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 800-1300g / g.

[0069] Step 4: UV anti-aging test

[0070] After the reaction, 1g of common super absorbent resin and super absorbent resin with spectral UV resistance were taken and placed in 2000mL water for natural soaking for 10h. The two saturated 10-20 mesh water-absorbing gels were placed in a UV aging test box. The test conditions were 280-400nm wavelength UV lamp irradiation, and the irradiance was 0.51W / m 2, the temperature is 40℃, continuous irradiation, sampling and photography are taken every half an hour to observe the status.

[0071] The test results show that the water-absorbent resin without anti-ultraviolet additives is completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives fumed silica and avobenzone, and ultraviolet absorbers UV-312 and UV-3638 is not completely degraded for up to 12 hours; and the solid content of the common super absorbent resin after 2 hours of irradiation is only 8.87% of the original solid content, while the super absorbent resin with improved gel strength and broad-spectrum anti-ultraviolet prepared by this patent (prepared in Example 12) has a solid content of 86.74% before irradiation after 12 hours of irradiation. This shows that the anti-ultraviolet effect is obvious (such as Figure 7 shown).

[0072] The method for gel strength is referred to the literature (Yang Yuhua, Ji Hongjian, Pan Zhenyuan, Jia Hengtao, Hua Rong. Determination of gel strength of super absorbent resin [J]. Applied Chemistry, 1993 (03): 112-113.). The gel strength of the hydrogel prepared by the general method when the particle size is 20 mesh is 10-30 kPa, while the gel strength of the super absorbent resin prepared by the method of the embodiment of the present invention when the particle size is 20 mesh is 2-5 times that of the hydrogel prepared by the general method, and can reach up to 150 kPa.

[0073] Under the condition that other operating conditions remain unchanged, the present invention investigates the effect of the mass ratio of monomer (total mass of acrylic acid and acrylamide) to matrix (carboxymethyl reed cellulose) on water absorption, and the results are as follows: Figure 2 As shown in the figure: when the mass ratio of monomer to matrix is ​​3:2, the water absorption rate reaches the highest. The present invention investigates the effect of the mass ratio of acrylic acid to acrylamide on the water absorption rate, and the results are as follows: Figure 3 As shown in Figure 2, when the mass ratio of acrylic acid to acrylamide is 10:3, the water absorption rate reaches the highest. The present invention investigates the effect of the neutralization degree of acrylic acid on the water absorption rate, and the results are as follows: Figure 4 As shown: When the degree of neutralization of acrylic acid is 60%, the water absorption rate reaches the highest. The present invention also investigates the effect of the amount of crosslinking agent (90 mg, 150 mg, 200 mg, 250 mg, 300 mg, 350 mg, 400 mg) on ​​the water absorption rate. The results are as follows Figure 5 As shown in the figure: when the amount of cross-linking agent N,N-methylenebisacrylamide is 250 mg (relative to the acrylic acid monomer content of 30 g), the water absorption rate reaches the highest. The present invention also investigates the effect of the total amount of oxidant and reducing agent (and the amount of initiator, the ratio of oxidant to reducing agent is 1:1) on the water absorption rate, and the results are as follows: Figure 6As shown: when the amount of initiator is 700 mg (relative to the acrylic acid monomer content of 30 g), the water absorption rate reaches the highest. Therefore, the optimal preparation conditions of the present invention are: the neutralization degree of acrylic acid is 60%, the amount ratio of the crosslinking agent to 30 parts of acrylic acid monomer is 0.25, and the amount ratio of the initiator to 30 parts of acrylic acid monomer is 0.7.

[0074] The advantages of the present invention are:

[0075] 1. The inorganic UV shielding agents, fumed silica and nano zinc oxide, are used to shield UV-A rays (UV-A, wavelength 400-315nm) and UV-B rays (UV-B, wavelength 315-280nm). The fumed silica has excellent performance and can act as a cross-linking agent on the gel surface to effectively enhance the gel strength. The selected UV absorber, avobenzone, has a good absorption effect on UV-A rays, and the UV absorbers, UV-312 and UV-3638, have a good absorption effect on UV-B rays. The combination of the two has a broad-spectrum anti-UV performance, can significantly absorb unshielded UV rays, and avoid the breakage and aging of the molecular chains of the super absorbent resin;

[0076] 2. Selecting redox initiators ammonium persulfate and sodium bisulfite in the preparation process can reduce the free energy of decomposition of ammonium persulfate, control the polymerization temperature at around 45°C, ensure smooth polymerization and reduce explosion, and reduce energy consumption;

[0077] 3. A slightly excessive amount of sodium bisulfite in the polymerization process can act as an antioxidant, and will not significantly affect the water absorption rate. There is no need to add additional antioxidants, which reduces costs and simplifies the preparation process;

[0078] 4. Fumed silica, avobenzone, UV absorbers UV-312 and UV-3638 are easy to disperse and will not significantly change the water absorption rate, but the gel strength is enhanced, the UV resistance wavelength range is wide, and the anti-UV effect is significant.

[0079] 5. The entire experimental process is prepared using a one-pot method, which does not require post-processing, simplifies the experimental steps, and has a water absorption rate of more than 800 times, which is significantly higher than that of market products.

[0080] The embodiments of the present application will be described in detail below. This embodiment is implemented on the premise of the technical solution of the present application, and a detailed implementation method and a specific operation process are given, but the protection scope of the present application is not limited to the following embodiments.

[0081] Example 1

[0082] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 50mL of a pre-prepared 10% w / v sodium hydroxide solution is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 30%, and the mixture is stirred while dropping until it returns to room temperature. Then 0.3g of fumed silica powder, 12g of carboxymethyl reed cellulose, 6g of acrylamide, and 0.1g of nano zinc oxide are added to the neutralized solution, and after stirring evenly, 0.03g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.03g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.03g of avobenzone are added thereto in sequence. After stirring for 20 minutes, add 0.090g of cross-linking agent N,N-methylenebisacrylamide and 0.25g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.25g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 1.5 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The super absorbent resin has a water absorption rate of 800g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 10% after 4 hours, indicating that the anti-ultraviolet effect was obvious.

[0083] Example 2

[0084] At 0°C, add 30g of acrylic acid monomer from which the inhibitor has been removed to the reaction container, add 66mL of a 10% sodium hydroxide solution prepared in advance to the acrylic acid dropwise, so that the neutralization degree of the acrylic acid is 40%, and stir while dropping until it returns to room temperature. Then add 0.35g of fumed silica powder, 13g of carboxymethyl reed cellulose, 6.5g of acrylamide, and 0.15g of nano zinc oxide to the neutralized solution, add 0.035g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.035g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.035g of avobenzone to the neutralized solution, stir evenly, and then add 0.035g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.035g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.035g of avobenzone. After stirring for 20 minutes, add 0.090g of cross-linking agent N,N-methylenebisacrylamide and 0.25g of oxidant ammonium persulfate in turn, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.25g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 1.5 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 870g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, and the irradiation was continuous. Samples were taken and photographed every half an hour to observe the status. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 13% after 4.5 hours, indicating that the anti-ultraviolet effect was obvious.

[0085] Example 3

[0086] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 66mL of a 10% sodium hydroxide solution prepared in advance is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 40%, and the mixture is stirred while dropping until it returns to room temperature. Then 0.35g of fumed silica powder, 14g of carboxymethyl reed cellulose, 6.5g of acrylamide, and 0.18g of nano zinc oxide are added to the neutralized solution, and after stirring evenly, 0.035g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.035g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.035g of avobenzone are added thereto in sequence. After stirring for 20 minutes, add 0.105g of cross-linking agent N,N-methylenebisacrylamide and 0.30g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.30g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 1.5 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 925g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 18% after 4.5 hours, indicating that the anti-ultraviolet effect was obvious.

[0087] Example 4

[0088] At 0°C, add 30g of acrylic acid monomer from which the inhibitor has been removed to the reaction container, add 66mL of a 10% sodium hydroxide solution prepared in advance to the acrylic acid dropwise, so that the neutralization degree of the acrylic acid is 40%, and stir while dropping until it returns to room temperature. Then add 0.40g of fumed silica powder, 15g of carboxymethyl reed cellulose, 7g of acrylamide, and 0.2g of nano zinc oxide to the neutralized solution, add to the neutralized solution, stir evenly, and then add 0.05g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.05g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.05g of avobenzone. After stirring for 20 minutes, add 0.12g of cross-linking agent N,N-methylenebisacrylamide and 0.35g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.35g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 1.5 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 970g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, and the irradiation was continuous. Samples were taken and photographed every half an hour to observe the status. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 21% after 6 hours, indicating that the anti-ultraviolet effect was obvious.

[0089] Example 5

[0090] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 83mL of a 10% sodium hydroxide solution prepared in advance is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 50%, and the mixture is stirred while dropping until it returns to room temperature. Then 0.45g of fumed silica powder, 13.5g of carboxymethyl reed cellulose, 7.5g of acrylamide, and 0.23g of nano zinc oxide are added to the neutralized solution, and then 0.05g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.05g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.05g of avobenzone are added to the neutralized solution, and stirred evenly. After stirring for 20 minutes, add 0.15g of cross-linking agent N,N-methylenebisacrylamide and 0.40g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.40g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 1040g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 24% after 5 hours, indicating that the anti-ultraviolet effect was obvious.

[0091] Example 6

[0092] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 100mL of a 10% sodium hydroxide solution prepared in advance is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 60%, and the mixture is stirred while dropping until it returns to room temperature. Then 0.5g of fumed silica powder, 16g of carboxymethyl reed cellulose, 8g of acrylamide, and 0.28g of nano zinc oxide are added to the neutralized solution, and after stirring evenly, 0.08g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.08g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.08g of avobenzone are added thereto in sequence. After stirring for 20 minutes, add 0.15g of cross-linking agent N,N-methylenebisacrylamide and 0.40g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.40g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 1095g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, and the irradiation was continuous. Samples were taken and photographed every half an hour to observe the status. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 25% after 6 hours, indicating that the anti-ultraviolet effect was obvious.

[0093] Example 7

[0094] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 100mL of a 10% sodium hydroxide solution prepared in advance is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 60%, and the mixture is stirred while dropping until it returns to room temperature. Then 0.6g of fumed silica powder, 17g of carboxymethyl reed cellulose, 8.5g of acrylamide, and 0.3g of nano zinc oxide are added to the neutralized solution, and after stirring evenly, 0.10g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.10g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.10g of avobenzone are added thereto in sequence. After stirring for 20 minutes, add 0.18g of cross-linking agent N,N-methylenebisacrylamide and 0.45g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.45g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 1130g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 26% after 6.5 hours, indicating that the anti-ultraviolet effect was obvious.

[0095] Example 8

[0096] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 116mL of a 10% sodium hydroxide solution prepared in advance is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 70%, and the mixture is stirred while dropping until it returns to room temperature. Then 0.8g of fumed silica powder, 18g of carboxymethyl reed cellulose, 8.5g of acrylamide, and 0.35g of nano zinc oxide are added to the neutralized solution, and after stirring evenly, 0.15g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.15g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.15g of avobenzone are added thereto in sequence. After stirring for 20 minutes, add 0.25g of cross-linking agent N,N-methylenebisacrylamide and 0.50g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.50g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 1185g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 27% after 7 hours, indicating that the anti-ultraviolet effect was obvious.

[0097] Example 9

[0098] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 133mL of a 10% sodium hydroxide solution prepared in advance is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 80%, and the mixture is stirred while dropping until it returns to room temperature. Then 1.0g of fumed silica powder, 20g of carboxymethyl reed cellulose, 9g of acrylamide, and 0.4g of nano zinc oxide are added to the neutralized solution, and after stirring evenly, 0.20g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.20g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.20g of avobenzone are added thereto in sequence. After stirring for 20 minutes, add 0.35g of cross-linking agent N,N-methylenebisacrylamide and 0.55g of oxidant ammonium persulfate in turn, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.55g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 1240g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 27% after 8 hours, indicating that the anti-ultraviolet effect was obvious.

[0099] Example 10

[0100] At 0°C, add 30g of acrylic acid monomer from which the inhibitor has been removed to the reaction container, add 100mL of a 10% sodium hydroxide solution prepared in advance to the acrylic acid dropwise, so that the neutralization degree of the acrylic acid is 60%, and stir while dropping until it returns to room temperature. Then add 1.25g of fumed silica powder, 26g of carboxymethyl reed cellulose, 9g of acrylamide, and 0.5g of nano zinc oxide to the neutralized solution, add 0.25g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.25g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.25g of avobenzone to the neutralized solution, stir evenly, and then add 0.25g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.25g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.25g of avobenzone. After stirring for 20 minutes, add 0.25g of cross-linking agent N,N-methylenebisacrylamide and 0.35g of oxidant ammonium persulfate in sequence, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.35g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The super absorbent resin has a water absorption rate of 1300g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 58% after 12 hours, indicating that the anti-ultraviolet effect was obvious.

[0101] Embodiment 11

[0102] At 0°C, 30g of acrylic acid monomer from which the inhibitor has been removed is added to the reaction container, and 100mL of a 10% sodium hydroxide solution prepared in advance is added dropwise to the acrylic acid to make the neutralization degree of the acrylic acid 60%, and the mixture is stirred while dropping until it returns to room temperature. Then 1.25g of fumed silica powder, 20g of carboxymethyl reed cellulose, 10g of acrylamide, and 0.6g of nano zinc oxide are added to the neutralized solution, and after stirring evenly, 0.30g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.30g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.30g of avobenzone are added thereto in sequence. After stirring for 20 minutes, add 0.25g of cross-linking agent N,N-methylenebisacrylamide and 0.30g of oxidant ammonium persulfate in turn. After stirring and passing nitrogen for 30 minutes, move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.30g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 1285g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 38% after 10 hours, indicating that the anti-ultraviolet effect was obvious.

[0103] Example 12

[0104] At 0°C, add 30g of acrylic acid monomer from which the inhibitor has been removed to the reaction container, add 100mL of a 10% sodium hydroxide solution prepared in advance to the acrylic acid dropwise, so that the neutralization degree of the acrylic acid is 60%, and stir while dropping until it returns to room temperature. Then add 1.5g of fumed silica powder, 20g of carboxymethyl reed cellulose, 12g of acrylamide, and 0.7g of nano zinc oxide to the neutralized solution, add 0.30g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.30g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.30g of avobenzone to the neutralized solution, stir evenly, and then add 0.30g of ultraviolet absorber N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide (UV-312), 0.30g of ultraviolet absorber 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one (UV-3638), and 0.30g of avobenzone. After stirring for 20 minutes, add 0.25g of cross-linking agent N,N-methylenebisacrylamide and 0.25g of oxidant ammonium persulfate in turn, stir and pass nitrogen for 30 minutes, then move the reaction container into a 45°C water bath, inject the deoxygenated reducing agent sodium bisulfite solution (NaHSO3 mass is 0.25g) into the reaction system with a syringe, continue stirring and react until the system gradually becomes viscous, then stop stirring, raise the water bath temperature to 95°C and keep warm for 2 hours. After the reaction is completed, place the prepared super absorbent resin in an oven and dry it for 48 hours, and then crush it to obtain a super absorbent resin product with the desired particle size, improved gel strength and broad-spectrum UV resistance. The water absorption rate of this super absorbent resin is 1265g / g. The 10-20 mesh absorbent gel after water absorption is placed in a UV aging test box. The test conditions are 280-400nm wavelength UV lamp irradiation, and the irradiance is 0.51W / m 2 The temperature was 40°C, the irradiation was continuous, samples were taken and photographed every half an hour, and the status was observed. The test results showed that the water-absorbent resin without anti-ultraviolet additives was completely degraded after 2 hours, while the water-absorbent resin with anti-ultraviolet additives had a remaining solid content of 43% after 11 hours, indicating that the anti-ultraviolet effect was obvious.

[0105] The present invention has many specific application paths, and the above is only a preferred embodiment of the present invention. It should be pointed out that the above embodiments are only used to illustrate the present invention, and are not used to limit the protection scope of the present invention. For those of ordinary skill in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a highly absorbent resin having improved gel strength and broad-spectrum UV resistance, characterized in that: The following steps are involved: A. Add a neutralizing agent to the acrylic acid monomer and stir while adding the neutralizing agent; B. After the reaction of step A is completed, carboxymethyl reed cellulose, acrylamide, fumed silica, nano zinc oxide, organic anti-ultraviolet additive, crosslinking agent and oxidant are added in sequence, stirred and ventilated with nitrogen, and then a reducing agent is added to react with stirring; C. After the reaction of step B is completed, the temperature is raised to 90-100°C and kept for 1.5-2.5 h to obtain; The neutralizing agent is sodium hydroxide; after the neutralizing agent is added in step A, the neutralization degree of acrylic acid is 60%; The mass ratio of the acrylic acid monomer, neutralizer, carboxymethyl reed cellulose, acrylamide, fumed silica, nano zinc oxide, organic anti-ultraviolet additive, crosslinking agent, oxidant and reducing agent is 30:10:26:9:1.25:0.5:0.75:0.25:0.35:0.35; The organic anti-ultraviolet additive is N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide, 2,2'-(1,4-phenylene)bis-4H-3,1-benzoxazine-4-one and avobenzone in a mass ratio of 1:1:1; The preparation method of carboxymethyl reed cellulose comprises the following steps: mixing crushed reed powder with a low-concentration alkali solution, stirring for 3-5 hours, then adding a high-concentration alkali solution and continuing to stir for 1-3 hours; and then adding sodium chloroacetate to carry out etherification reaction to obtain carboxymethyl reed cellulose; The degree of substitution of the carboxymethyl reed cellulose is 0.

43.

2. The method for preparing a highly water-absorbent resin having improved gel strength and broad-spectrum UV resistance according to claim 1, characterized in that: The cross-linking agent is N,N-methylenebisacrylamide; The oxidizing agent is ammonium persulfate; the reducing agent is sodium bisulfite.

3. The method for preparing a super absorbent resin having improved gel strength and broad-spectrum UV resistance according to claim 1, characterized in that: The low concentration alkaline solution is a 4-5% sodium hydroxide solution, and the high concentration alkaline solution is a 14-16% sodium hydroxide solution; the stirring temperature is 35°C; The mass ratio of the reed powder to the alkali in the low-concentration alkali solution and the alkali in the high-concentration alkali solution is 100:22.5:30; The reaction temperature of the etherification reaction is 75° C. and the reaction time is 2-3 h; the mass ratio of the reed powder to sodium chloroacetate is 100:

50.

4. A highly water-absorbent resin having improved gel strength and broad-spectrum UV resistance prepared by the method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Multiple-effect super absorbent resin fertilizer and manufacturing method thereof

    CN103694052A

  • Method for preparing super absorbent resin by grafting and copolymerizing carboxymethyl potato pulp

    CN104072669A

  • Method for preparing super absorbent resin by carboxymethyl bagasse

    CN104163895A

Cited By

  • White and thick high-absorptivity resin and preparation method thereof

    CN120795225A